GRP78 Protein Expression as Prognostic Values in Neoadjuvant Chemoradiotherapy and Laparoscopic Surgery for Locally Advanced Rectal Cancer - Lee, Hee Yeon; Jung, Ji-Han; Cho, Hyun-Min; Kim, Sung Hwan; Lee, Kang-Moon; Kim, Hyung-Jin; Lee, Jong Hoon; Shim, Byoung Yong (Cancer research and treatment, 2015)
We investigated the relationships between biomarkers related to endoplasmic reticulum stress proteins (glucose-regulated protein of molecular mass 78 [GRP78] and Cripto-1 [teratocarcinoma-derived growth factor 1 protein]), pathologic response, and prognosis in locally advanced rectal cancer. All clinical stage II and III rectal cancer patients received 50.4 Gy over 5.5 weeks, plus 5-fluorouracil (400 mg/m(2)/day) and leucovorin (20 mg/m(2)/day) bolus on days 1 to 5 and 29 to 33, and surgery was performed at 7 to 10 weeks after completion of all therapies. Expression of GRP78 and Cripto-1 proteins was determined by immunohistochemistry and was assessed in 101 patients with rectal cancer treated with neoadjuvant chemoradiotherapy (CRT). High expression of GRP78 and Cripto-1 proteins was observed in 86 patients (85.1%) and 49 patients (48.5%), respectively. Low expression of GRP78 protein was associated with a significantly high rate of down staging (80.0% vs. 52.3%, respectively; p=0.046) and a significantly low rate of recurrence (0% vs. 33.7%, respectively; p=0.008) compared with high expression of GRP78 protein. Mean recurrence-free survival according to GRP78 expression could not be estimated because the low expression group did not develop recurrence events but showed a significant correlation with time to recurrence, based on the log rank method (p=0.007). GRP78 also showed correlation with overall survival, based on the log rank method (p=0.045). GRP78 expression is a predictive and prognostic factor for down staging, recurrence, and survival in rectal cancer patients treated with 5-fluorouracil and leucovorin neoadjuvant CRT.